Cockroach rules - Dunstan, Matthew (Macmillan Education Australia South Yarra, 1998)
Cockroach Rules by Matthew Dunstan is a children's book that tells the story of a cockroach who becomes the unlikely hero of a school adventure. When a group of kids discovers that their school is in trouble, they enlist the help of a clever and resourceful cockroach. Together, they embark on a mission to save their school from impending doom. The book combines humor and excitement as the characters navigate various challenges, learning about teamwork, bravery, and thinking outside the box. Dunstan's engaging narrative and lively illustrations make this a delightful read for young audiences.